2013
DOI: 10.21608/jssae.2013.52897
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN EFFECIENCY IN BARELY UNDER SALINE-SODIC CONDITIONDS AS AFFECTED BY UREA, COMPOST AND BIOFERTILIZER (Rhizobium radiobacter sp.)

Abstract: Effects of application of different rates of urea, biofertilizer, (Rhizobium radiobacter sp.) as salt tolerant PGPR strain and compost on barley (Hordeum valgare L. cv. Giza 126) were studied on a saline-sodic sandy loam soil at Gelbana village, Northern Sinai Governorate, Egypt during the two successive winter seasons of 2011/2012 and 2012/2013. The studied treatments were No, control (non fertilized), N1, mineral-N (119 kg N ha-1), N2, mineral-N (179 kg N ha-1), equivalent 0 , 50 and 75% from recommended rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
8
7
0
Order By: Relevance
“…These results are in a harmony with those obtained by Abdel Lattif (2007) and Poraas et al, (2009). These results are in agreement with those obtained by Shaban et al (2012) and Helmy et al (2013a).…”
Section: Soil Ph and Soil Salinity (Ec E )supporting
confidence: 94%
“…These results are in a harmony with those obtained by Abdel Lattif (2007) and Poraas et al, (2009). These results are in agreement with those obtained by Shaban et al (2012) and Helmy et al (2013a).…”
Section: Soil Ph and Soil Salinity (Ec E )supporting
confidence: 94%
“…The highest NUE value 12.9 g gP -1 P was obtained in calcareous soil when plants treated with 50 mg N as AS kgP -1 P soil + Mic., while the highest NUE value 8.38 g gP -1 P was obtained in sandy soil when plants sprayed with compost tea plus the low rate of AS, N2 (50 mg N kgP -1 P soil) which increased the efficiency use of AS fertilizer by 71.0% compared with the treatment received AS (50 mg N kgP -1 P soil) solely. These results are in agreement with those obtained by Helmy et al (2013).…”
Section: Protein Contentsupporting
confidence: 93%
“…For 1000-grain weight, data indicated that, the highest 1000-grains weight was recorded in plants treated with mineral nitrogen only with averages of 50.63 and 55.33 g in both seasons, respectively. These results were supported by those obtained by Helmy et al (2013)who reported that, application of 119 kg N. ha -1 and 179 kg N. ha -1 increased1000-grain weight by 22.0% and 35.8% in 2011/2012 and18.6% and 30.7% in 2012/2013, respectively. These results showed the positive effect of urea, which stimulates the decomposers of organic matter thereby, releases the nutrients in an available form.…”
Section: Yield and Its Componentssupporting
confidence: 88%
“…This result could be attributed to the role of nitrogen on barley growth and yield components which in turn reflected on straw and grain yields fad -1 . Helmy et al (2013) noticed that the treated Quinoa plants with nitrobin alone induced significant decreases in seed yield/plant in both growing seasons. These results were supported by Filho et al, (2013)whose reported that, A. brasilense alone was not effective enough to replace the entire nitrogen fertilization but, combination with nitrogen fertilization, made it possible to give the highest yields of wheat grains.…”
Section: Yield and Its Componentsmentioning
confidence: 98%